2014
DOI: 10.1155/2014/479187
|View full text |Cite
|
Sign up to set email alerts
|

Silver Binding Nucleolar Organizer Regions Dots in Oral Leukoplakia with Epithelial Dysplasia and Oral Squamous Cell Carcinoma: An In Vivo Study

Abstract: Silver binding nucleolar organizer regions (AgNOR) in normal oral mucosa (NOM), oral leukoplakia with epithelial dysplasia (ED), and oral squamous cell carcinoma (OSCC) were studied. The mean AgNOR count per nucleus increased from NOM to ED to OSCC. Tissue showing ED in oral leukoplakia and OSCC cases showed higher counts, wider scatter, and smaller size of AgNOR dots in the nuclei. The study seems to suggest that time method has some potential in distinguishing between NOM and oral leukoplakia with ED and OSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…While hematoxylin and eosin staining is commonly employed for the histological diagnosis of carcinomas, there are cases where the histopathological characteristics may not offer adequate clarity in determining the precise nature of these tumors. Alternative methods, such as the silver colloid method for staining NORs inside the nucleus, have shown to be more useful histochemical techniques that offer further insights into the cellular situation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…While hematoxylin and eosin staining is commonly employed for the histological diagnosis of carcinomas, there are cases where the histopathological characteristics may not offer adequate clarity in determining the precise nature of these tumors. Alternative methods, such as the silver colloid method for staining NORs inside the nucleus, have shown to be more useful histochemical techniques that offer further insights into the cellular situation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that the number of NORs/nucleus increases from the ED to OSCC [ 15 , 16 , 18 , 20 , 24 , 25 ]. Considering the WHO classification of dysplasia, an increasing of indexes of AgNORs from lesions with lower degrees of dysplasia to lesions with more severe dysplasia [ 26 ] has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%